Knowledge and practice regarding prevention of puerperal sepsis among postpartum women attending a private hospital in Bangladesh - Sultana, Shirin; Methe, Fatema Zohora; Muhammad, Faisal; Chowdhury, ABM Alauddin (International Journal of Research in Medical Sciences, 2018)
Background: Puerperal sepsis is a common pregnancy-related condition that could eventually lead to obstetric shock or sometimes death. In developing world, the puerperal sepsis is the second most cause of maternal mortality. Cases of Maternal mortality have not declined in spite of efforts by both the public and private sector to prevent such deaths. Methods: A descriptive cross-sectional study was conducted among 150 postpartum mothers who attended Ibn Sina Medical College Hospital (ISMCH) Bangladesh during August to December 2017. A non-probability purposive sampling technique was used to select the study participants and the data was collected using pre-tested semi-structured questionnaire by face to face interview. The collected information was analysed using SPSS 22.0 version. Results: About 50.7% of the study participants were in the age group 19-29 years and the mean age of the study participants was 29.6±15.9 years. More than seven-tenths (73.3%) of the study participants were Muslims and the majority (24.7%) of the study participants had senior secondary certificate. Most of the study participants (62%) were living in urban area and only 18.7% were service holders. Only 39.3% of the respondents think that they have sufficient knowledge regarding prevention of puerperal sepsis and about 78% of the study participants mentioned that getting immediate medical care for any wounds or even seasonal diseases prevents puerperal sepsis. About 37.4% were disagreed to avoid sexual intercourse during last 2 months of pregnancy prevents puerperal sepsis and about 51.3% were agreed to avoid appearances in crowded and unhygienic places, this will prevent from catching respiratory diseases. Conclusions: The findings reported that most of the study participants had poor level of knowledge regarding prevention of puerperal sepsis. However, the study participants had satisfactory practice level about prevention of puerperal sepsis. It further reveals that educational level and age of the study participants was found statistically significant with knowledge about prevention of puerperal sepsis.